1988
DOI: 10.3171/jns.1988.68.2.0259
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistological evaluation of macrophage infiltrates in brain tumors

Abstract: Peritumoral edema is one of the most serious complications of intracranial neoplasms; however, the exact pathogenesis of this condition is still unknown. To explore the effect of macrophages in brain tumors on the pathogenesis of peritumoral edema, 42 specimens of primary or metastatic brain tumors were studied. Frozen sections were examined by an immunoperoxidase staining technique with anti-Leu-M3 monoclonal antibody. Eight of 14 gliomas demonstrated Leu-M3-positive cell (macrophage) infiltration. The two gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(52 citation statements)
references
References 30 publications
1
51
0
Order By: Relevance
“…Microglia is abundant in the tumour-free CNS and comprises between 5% and 10% (depending on region) of all brain cells [71,83]; for comparison -the density of neurons is approximately 20% of cells in the human brain [57]. In GBM the number of TAM can be very high and constitutes up to 30% of the tumour mass [5,161,138,125], in medulloblastomas even 80% of all intra-tumoural cells can carry myeloid cell markers [138]. We observed that the distribution of TAM in GBM is very heterogeneous and the average number of these cells is between 20% and 30% (M. Synowitz and R. Glass, unpublished data).…”
Section: Accumulation Of Myeloid Cells In Gliomasmentioning
confidence: 99%
“…Microglia is abundant in the tumour-free CNS and comprises between 5% and 10% (depending on region) of all brain cells [71,83]; for comparison -the density of neurons is approximately 20% of cells in the human brain [57]. In GBM the number of TAM can be very high and constitutes up to 30% of the tumour mass [5,161,138,125], in medulloblastomas even 80% of all intra-tumoural cells can carry myeloid cell markers [138]. We observed that the distribution of TAM in GBM is very heterogeneous and the average number of these cells is between 20% and 30% (M. Synowitz and R. Glass, unpublished data).…”
Section: Accumulation Of Myeloid Cells In Gliomasmentioning
confidence: 99%
“…Some of the histological studies on microglia and macrophage infiltration attempted to make correlations of type or intensity of myeloid cell infiltration and tumour type or grade (Nishie et al, 1999;Roggendorf et al, 1996;Rossi et al, 1988;1987): there was a tendency for greater infiltration of high grade tumours such as glioblastoma. Higher myeloid cell infiltration was proposed to correlate with peritumoural oedema (Shinonaga et al, 1988), but not with survival in one early study (Rossi et al, 1989). Our contemporary understanding of the complexity of the myeloid cell compartment in the brain that we have discussed in section 2 predicts that correlation of survival and simple myeloid cell phenotyping and quantification is improbable.…”
Section: Identification Of Microglia and Macrophages In Brain Tumoursmentioning
confidence: 90%
“…Subsequent studies were able to profit from monoclonal antibodies to better define myeloid cells, not only in suspension, but also in tissue sections. In histological sections, quantification is somewhat more challenging and difficult to compare between studies, but reports from several groups using panels of different antibodies described significant myeloid cell infiltration in low grade glioma (Rossi et al, 1988;Shinonaga et al, 1988), high grade glioma (Rossi et al, 1987;1989;Shinonaga et al, 1988), as well as metastatic brain tumours (Shinonaga et al, 1988). Moreover, although flow cytometric analysis on single-cell suspensions of digested human tumour confirmed these findings, they did not allow an unequivocal distinction of microglia and other brain macrophages (Parney et al, 2009;Watters et al, 2005).…”
Section: Identification Of Microglia and Macrophages In Brain Tumoursmentioning
confidence: 99%
“…Immunohistological studies have demonstrated macrophage accumulation in and around human tumors associated with edema. 28 Inflammatory cells such as polymorphonuclear leukocytes and macrophages possess impressive arsenals consisting of at least four major components. 2930 These are the release of specific enzymes and other reactive components from specialized granules; the release of platelet activating factor (PAF); 31 the formation of specific arachidonic acid products, the eicosanoids, and the generation of superoxide anion radical and the resultant family of reactive products.…”
Section: Inflammatory Processmentioning
confidence: 99%